1991
DOI: 10.1116/1.577134
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature (∼400 °C) growth of polycrystalline diamond films in the microwave plasma of CO/H2 and CO/H2/Ar systems

Abstract: Articles you may be interested inReal time spectroellipsometry for optimization of diamond film growth by microwave plasmaenhanced chemical vapor deposition from CO/H2 mixtures Flattened diamond crystals synthesized by microwave plasma chemical vapor deposition in a COH2 systemThe role of hydrogen in diamond synthesis using a microwave plasma in a CO/H2 system In order to elucidate the growth conditions for pure diamond of good crystallinity, the correlation of the properties of deposited films and gas phase s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Oxygen (in the form of CO, O 2 , or alcohol) to the CVD reaction gases has not only a beneficial effect on the growth rate and quality of the diamond films but also allows low-temperature diamond growth [ 109 ]. It was found that oxygen has only a minor effect on the mole fractions of radical species such as H and CH 3 [ 110 ].…”
Section: Diamond Nucleation and Growthmentioning
confidence: 99%
“…Oxygen (in the form of CO, O 2 , or alcohol) to the CVD reaction gases has not only a beneficial effect on the growth rate and quality of the diamond films but also allows low-temperature diamond growth [ 109 ]. It was found that oxygen has only a minor effect on the mole fractions of radical species such as H and CH 3 [ 110 ].…”
Section: Diamond Nucleation and Growthmentioning
confidence: 99%